Selected pathobiological features and principles of pharmacological pain management. Issue 5 (May 2020) - Khammissa, Razia Abdool Gafaar; Ballyram, Raoul; Fourie, Jeanine; Bouckaert, Michael; Lemmer, Johan; Feller, Liviu
Pain induced by inflammation and nerve injury arises from abnormal neural activity of primary afferent nociceptors in response to tissue damage, which causes long-term elevation of the sensitivity and responsiveness of spinal cord neurons. Inflammatory pain typically resolves following resolution of inflammation; however, nerve injury—either peripheral or central—may cause persistent neuropathic pain, which frequently manifests as hyperalgesia or allodynia. Neuralgias, malignant metastatic bone disease, and diabetic neuropathy are some of the conditions associated with severe, often unremitting chronic pain that is both physically and psychologically debilitating or disabling. Therefore, optimal pain management for patients with chronic neuropathic pain requires a multimodal approach that comprises pharmacological and psychological interventions. Non-opioid analgesics (e.g., paracetamol, aspirin, or other non-steroidal anti-inflammatory drugs) are first-line agents used in the treatment of mild-to-moderate acute pain, while opioids of increasing potency are indicated for the treatment of persistent, moderate-to-severe inflammatory pain. N-methyl D-aspartate receptor antagonists, antidepressants, anticonvulsants, or a combination of these should be considered for the treatment of chronic neuropathic pain. This review discusses the various neural signals that mediate acute and chronic pain, as well as the general principles of pain management.